THE FORECAST OF CHANGE OF GROUNDWATER LEVEL IN THE ABSENCE OF DRAINAGE SYSTEM: (on the example of the Ararat Valley) (Proceedings of the YSU C: Geological and Geographical Sciences, 2019)
In the article, taking into account the geofiltration scheme of the Ararat Valley, an analytical method has been used to predict the change of groundwater level in irrigated lands located outside the drainage zone. Calculations have shown that in areas beyond the influence of the drainage network, the rise of groundwater level during the growing season in the first quarter of the year reaches 2.5 m. In the conditions of the Ararat valley intensive evaporation of groundwater occurs, which leads to a deterioration of the ameliorative state of irrigated lands. Thus, in order to lower and maintain the groundwater table at a critical depth, the construction of a drainage system is a prerequisite.
Keywords: Ararat Valley; groundwater level; forecasting; analytical method; drainage system; irrigated lands